Influence of Particle and Air-Abrasion Moment on Y-TZP Surface Characterization and Bond Strength - Martins, Samira Branco [UNESP]; Abi-Rached, Filipe de Oliveira [UNESP]; Adabo, Gelson Luis [UNESP]; Baldissara, Paolo; Fonseca, Renata Garcia [UNESP] (Wiley-Blackwell, 2019)
Purpose To evaluate the influence of particle and air-abrasion on the surface characterization and shear bond strength (SBS) of a Y-TZP ceramic with a resin cement. Materials and Methods Y-TZP specimens were air-abraded with 50 mu m alumina particles; 120 mu m alumina particles; 30 mu m silica-coated alumina particles (Rocatec Soft); 110 mu m silica-coated alumina particles (Rocatec Plus). Air-abrasion was performed before (BS); after (AS); before and after (BAS) zirconia sintering. Surface characterization included roughness (n = 10), wettability (n = 10), morphology (n = 2), and elemental composition (n = 2). For SBS (n = 11), composite resin discs were bonded to the air-abraded and silane-treated zirconia surface, with the resin cement RelyX ARC. Failure mode was determined. Roughness, wettability, and SBS data were analyzed by two-way ANOVA with pairwise interaction and Tukey's test (alpha = 0.05). Results Air-abrasion performed with coarser particles at BS and BAS moments provided the highest roughness values, while the lowest roughness values were observed with particles combined with AS moment (p < 0.01). Rocatec Plus provided lower contact angle than the 120 mu m alumina particles (p = 0.013), and BAS exhibited lower contact angle than BS (p = 0.002). The combinations 120 mu m/BS and the silica-coated alumina particles/AS and /BAS showed the highest SBS (p < 0.05). The combination of each particle/BAS was statistically similar to the same particle/AS. Failure mode was 100% adhesive for all groups. The interaction particle size/air-abrasion moment determined the morphological pattern. Silicon was observed only in the Rocatec groups. Conclusions Roughness was influenced by the particle size and was higher when the zirconia was air-abraded in its green stage. The particle composition played an important role in the wettability and both studied air-abrasion moments provided similar wettability than the one in which air-abrasion is usually performed. The highest SBS values were observed in the three moments, by using certain particles for each moment.
Keywords: Dental ceramic; shear bond strength; roughness; tooth restoration; wettability